Magnetic microparticle-based multimer detection system for the detection of prion oligomers in sheep - Lim K (Dove Medical Press, 2015)
Kuntaek Lim,1 Su Yeon Kim,2 Byoungsub Lee,1 Christiane Segarra,3 Sungmin Kang,1 Youngran Ju,2 Mary Jo Schmerr,4 Joliette Coste,3 Sang Yun Kim,5 Takashi Yokoyama,6 Seong Soo A An7 1Department of Research and Development, PeopleBio Inc., 2Department of Arborbiology, Korean Center for Diseases and Control (KCDC), Seoul, Republic of Korea; 3Department of Blood Screening, Etablissement Français Du Sang (EFS), Montpellier, France; 4Ames Laboratories, US Department of Energy (USDOE), Iowa State University, Ames, IA, USA; 5Department of Neurology, Seoul National University Bundang Hospital, Sungnam-si, Republic of Korea; 6Department of Prion Research, National Institute of Animal Health, Tsukuba, Japan; 7Department of Bionano Technology, Gachon University, Sungnam-si, Republic of Korea Abstract: Transmissible spongiform encephalopathies (TSEs) are zoonotic fatal neurodegenerative diseases in animals and humans. TSEs are commonly known as bovine spongiform encephalopathy in cattle, scrapie in sheep and goats, chronic wasting disease in cervids, and Creutzfeldt–Jakob disease in humans. The putative transmissible agents are infectious prion proteins (PrPSc), which are formed by the conversion of the normal prion protein on the glycoprotein cell surface in the presence of other PrPSc. Reports of the transmission of TSEs through blood raised considerable concern about the safety of blood and blood products. To address this issue, many laboratories attempted to develop a sensitive and accurate blood diagnostic test to detect PrPSc. Previously, we reported that, compared to normal controls, the multimer detection system (MDS) was more efficient in detecting PrPSc in infected hamster brain homogenate, mouse plasma spiked with purified PrPSc from scrapie mouse brain, and scrapie-infected hamster plasmas. MDS differentiates prion multimers from the cellular monomer through the multimeric expression of epitopes on prion multimers, in contrast to the monomeric form. In this study, MDS detected PrPSc in plasma samples from scrapie-infected sheep expressing clinical symptoms, demonstrating 100% sensitivity and specificity in these samples. Plasma samples from asymptomatic lambs at the preclinical stage (8-month-old naturally infected offspring of scrapie-infected parents expressing a highly susceptible genotype) tested positive with 50% sensitivity and 100% specificity. In the first of two coded analyses using clinical scrapie-infected sheep and normal healthy samples, MDS successfully identified all but one of the clinical samples with 92% sensitivity and 100% specificity. Similar results were obtained in the second coded analysis using preclinical samples. MDS again successfully identified all but one of the samples with 87% sensitivity and 100% specificity. The false-negative sample was subjected to a protease pretreatment. In conclusion, MDS could accurately detect scrapie in plasma samples at both preclinical and clinical stages. From these studies, we conclude that MDS could be a promising tool for the early diagnosis of TSEs from blood samples. Keywords: transmissible spongiform encephalopathies, infectious prion proteins, normal prion protein, sensitivity, specificity, biomarker